Semiotics of Picture and News - مهدي عقيل (ALBAHITH ALALAMI, 2016)
It has become familiar to see alchemy as a methodological approach that combines conscious, diverse, psychological, social, structural, and discrete approaches in the communications technology that Marshall McLuhan found to be able to extend our bodies and senses, The media discourse has a deep and superficial structure produced by the first, with its social, cultural and historical backgrounds, in a context that connects the image with the word, as the "meanings are made" - everywhere, as described by Jonathan ) In fashion, in the arts as a whole, and from its "signs" Our analysis of «meaning», in the media, and communication through advertising, magazines, newspapers, television, and the Internet. Therefore, alchemy is preoccupied with how the signs work, their relation to each other and to the specific community, individuals and to each variable (ethnographic), which varies according to their culture and hobby. Which widens the field of alchemy to a wider range than its specific structure, but opens up to different codes, structures and conflicting ideologies where it reads (signs) in different ways and is compatible with other texts. Here, the semiotics impose a special methodological adjustment, because of the clash of the many meanings, and the intersection of them in one point, and one time, which makes us pursue these meanings, flowing, to take a position, or a specific interpretation or interpretation from different reception angles to the audience of readers, In the form of analysis and synthesis, and the reintroduction of the media (incident), in the multiplication of identities, their transformations, fixed and transformative patterns, virtual and virtual self-formation with the unrealistic, ) Come on To create the human of the present century for the broadcast of new values ​​in the media culture, and remain the active actor, between the actors of the methodology is also effective, as you intend to go into the problems, and explain one aspect of a coherent analytical approach.